Keterlibatan Selebriti Pasca Parliamentary Threshold dalam Kontestasi Politik Elektoral di Indonesia - Ritonga, Muslimin; Harahap, Raegen (Universitas Indo Global Mandiri, 2023)
This research aims to analyze celebrity involvement after the change in the Parliamentary Threshold of 4 percent which was first set in 2012 and implemented in the 2014 elections. Therefore, the implementation of the Parliamentary Threshold regulation actually brought controversy and criticism from various parties up to judicial review. One of the aspects that is considered controversial about the parliamentary threshold is that there are indications that it makes it difficult for political parties to contest in general elections, so that political parties are starting to recruit as many celebrities as possible, especially those placed in legislative elections. This research uses a qualitative-descriptive research approach with the library research method. Researchers collected research from 2011-2023 via Google Scholars related to celebrities or artists who participated in political contestations, especially in legislative general election contestations. From the data collection process, this research found two urgencies that had not been examined by previous research, (1) there was a change in the Parliamentary Threshold rules, resulting in political parties becoming more aggressive in involving celebrities in the Legislative Election contestation who were used as vote-getters to help vote. other political candidates. Second, political parties, in involving celebrities as legislative candidates, use the Son of the Soil strategy, namely being placed according to their respective regions, both in terms of place of birth and descent from the electoral district.